2019
DOI: 10.1515/htmp-2019-0001
|View full text |Cite
|
Sign up to set email alerts
|

Controllability of joint integrity and mechanical properties of friction stir welded 6061-T6 aluminum and AZ31B magnesium alloys based on stationary shoulder

Abstract: In order to improve joint integrity and reduce the amount of intermetallic compounds (IMCs), 6061-T6 Al and AZ31B Mg alloys were successfully joined by stationary shoulder friction stir welding (SSFSW). The stationary shoulder effectively enhanced the joint surface integrity and reduced the thickness reduction of the Al/Mg joint. The elimination of pin adhesion was beneficial to increasing material transfer and then improving interfacial joining length of Al/Mg joint. Extremely thin IMCs layer could be achieve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 29 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…The lap joints for the stationary shoulder have maximum shear load of 5.8KN, which is higher than that of the joints without stationary shoulder. Subsequently, the stationary shoulder is also successfully used for the Al/Mg butt joints [99]. The stationary shoulder can effectively prevent the outflow of plastic material.…”
Section: Innovative Variants Of Al/mg Fswmentioning
confidence: 99%
“…The lap joints for the stationary shoulder have maximum shear load of 5.8KN, which is higher than that of the joints without stationary shoulder. Subsequently, the stationary shoulder is also successfully used for the Al/Mg butt joints [99]. The stationary shoulder can effectively prevent the outflow of plastic material.…”
Section: Innovative Variants Of Al/mg Fswmentioning
confidence: 99%
“…The findings revealed that rotational speeds influence the parameters and tensile characteristics increased and subsequently declined as welding speed increased. The maximum tensile strength was 137 MPa at a welding speed of 60 mm/min [6]. The purpose of the study was to investigate the microstructural and corrosion behavior of FSW joints between a 6061 Al and AZ31 Mg with a zirconium interlayer.…”
Section: Introductionmentioning
confidence: 99%
“…The magnesium alloys have been widely used in the manufacture of aviation, automobile, and other fields, due to superior properties, such as high specific strength, good damping capacity, and easy recycle [1][2][3][4][5]. However, magnesium alloys have poor workability caused by the limited number of slip systems associated with a hexagonal, close-packed crystal structure [6].…”
Section: Introductionmentioning
confidence: 99%